2007
DOI: 10.1183/09031936.00162206
|View full text |Cite
|
Sign up to set email alerts
|

Scores of asthma and asthma severity reveal new regions of linkage in EGEA study families

Abstract: There is ongoing debate as to how asthma should be defined in order to forward understanding of the underlying mechanisms. The aim of the present study was to build quantitative scores of asthma and asthma severity and to assess whether refinement of disease phenotypes can facilitate the identification of chromosomal regions harbouring susceptibility genes.A genome-wide linkage scan was conducted in 110 families with at least two asthmatic siblings (n5508) from the French Epidemiological study on the Genetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Interestingly, analysis of different bin widths delineated a chromosomal region (63-83 cM) that overlaps a locus identified for severe asthma in German families 39 and is located at 10 cM from a linkage signal detected in the French EGEA study for an asthma severity score. 40 For SPT, the strongest evidence of linkage in the analysis of all families arose in the 3p25.3-q24 region. This evidence was not sustained when restricting the analysis to EUR families, suggesting that this region may harbour a major susceptibility gene that is involved in all populations.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, analysis of different bin widths delineated a chromosomal region (63-83 cM) that overlaps a locus identified for severe asthma in German families 39 and is located at 10 cM from a linkage signal detected in the French EGEA study for an asthma severity score. 40 For SPT, the strongest evidence of linkage in the analysis of all families arose in the 3p25.3-q24 region. This evidence was not sustained when restricting the analysis to EUR families, suggesting that this region may harbour a major susceptibility gene that is involved in all populations.…”
Section: Discussionmentioning
confidence: 98%
“…The approach that consists of combining clinical features with the level of asthma treatment to distinguish subgroups of subjects with a differential severity, as suggested by the GINA 2002 guidelines, has been suggested by epidemiological results in populations [20]. Furthermore, a genome-wide linkage analysis on asthma quantitative score conducted in the EGEA study showed that scoring asthma severity based on clinical items and asthma treatment increased power to detect linkage, compared with clinical items only [21].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of asthma is difficult to assess in epidemiological studies [25] and there is now a general consensus emerging that asthma is unlikely to be a single disease but different overlapping phenotypes [26]. It was recently shown that quantitative scores combining clinical items and treatment had good ability to detect risk factors by reducing misclassification of the disease status [27,28]. The new Global Initiative for Asthma (GINA) recommendations have evolved from severity to control and underlined the importance of asthma treatment [29].…”
Section: Discussionmentioning
confidence: 99%